Inverse perovskite cell containing self-assembled monomolecular layer and preparation method thereof

By using self-assembled single-layer materials and inorganic connecting layers in inverse perovskite solar cells, the problem of insufficient battery stability is solved, efficiency and stability are improved, and its competitiveness in real applications is enhanced.

CN119968010AActive Publication Date: 2025-05-09JIANGSU SHENGKAI NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510152445.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-05-09
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The stability of inverse perovskite solar cells is poor, which affects their application competitiveness in real scenarios.

Method used

Self-assembled single-molecular layer material is used as the hole transport layer, and a connecting layer composed of inorganic material is deposited thereon, enhancing the connection strength and stability between the perovskite layer and the hole transport layer.

Benefits of technology

It improves the photoelectric conversion efficiency and overall performance stability of perovskite solar cells, extends the service life of the battery, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119968010A_ABST
    Figure CN119968010A_ABST
Patent Text Reader

Abstract

The invention relates to an inversion perovskite cell containing a self-assembly monomolecular layer and a preparation method thereof.The perovskite cell comprises a hole transport layer, a perovskite layer, an electron transport layer and an electrode layer which are sequentially arranged from the side of a substrate, light is incident to the perovskite layer from the hole transport layer side, the hole transport layer is made of a self-assembly monomolecular layer material, and the electron transport layer is made of a self-assembly monomolecular layer material. A connecting layer is also arranged between the hole transport layer and the perovskite layer, an inorganic material is arranged in the connecting layer, and the inorganic material is one or combination of more of nitride, sulfide and oxide. According to the trans-perovskite cell, the self-assembled monomolecular material is adopted as the hole transport layer material, the energy level matching and conductivity requirements of trans-perovskite can be met, the connecting layer is deposited on the hole transport layer material, on one hand, the hole transport layer material can be firmly pressed on the substrate or the electrode layer, and on the other hand, the hole transport layer material can be firmly pressed on the substrate or the electrode layer; on the other hand, a bonding effect can be formed between the connecting layer and the perovskite layer, and the connecting strength between the connecting layer and the perovskite layer is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an inverse perovskite cell containing a self-assembled monomolecular layer and a preparation method thereof, and belongs to the field of photovoltaics. Background Art

[0002] As a clean energy source, solar energy can meet the growing global energy demand. Among many optoelectronic devices, perovskite solar cells have attracted much attention due to their high photoelectric conversion efficiency and low manufacturing cost. The theoretical efficiency limit of single-junction perovskite solar cells is about 31%, and the current laboratory record efficiency is 26.8%, which is comparable to that of crystalline silicon cells. The lifespan of crystalline silicon cells is 20-30 years, while the lifespan of the same perovskite cell is only 3-5 years, which seriously restricts the reduction of the levelized cost of electricity. Therefore, for perovskite cells, improving their stability is the current focus.

[0003] Perovskite cells are divided into two structures according to their stacked structure: formal (nip) and trans (pin). In the formal structure, since the use of spiro is unavoidable in the hole transport material of the formal cell, and spiro has great hygroscopicity and instability, the positive cell has poor stability. In contrast, the trans-type pin cell abandons the use of spiro and adopts other hole layers such as PTAA and SAMs. SAMs materials are widely concerned because of their thin thickness, low dosage, energy level matching, and good conductivity, and they have achieved the best conversion efficiency in perovskite cells. Compared with spiro, SAMs has a certain degree of improved stability. However, compared with PTAA (also a hole layer commonly used in the trans-type, which is a polymer), the stability performance of SAMs is still far behind. Therefore, while maintaining the high efficiency of SAMs materials in perovskite cells, its use stability can be further improved, so that perovskite cells have a competitive advantage over crystalline silicon in real scenarios. Summary of the invention

[0004] In order to improve the stability of an inverse perovskite battery, the present invention provides an inverse perovskite battery containing a self-assembled monolayer, and provides a preparation method of the battery. The inverse perovskite battery uses a self-assembled monolayer material as a hole transport layer material, which can meet the energy level matching and conductivity requirements of the inverse perovskite. A connecting layer is deposited on the hole transport layer material. On the one hand, the hole transport layer material can be firmly pressed on the substrate or electrode layer, and on the other hand, a bonding effect can be formed between the perovskite layer to enhance the connection strength between the connecting layer and the perovskite layer.

[0005] The technical solution adopted by the present invention is: an inverted perovskite battery containing a self-assembled monolayer, comprising a hole transport layer, a perovskite layer, an electron transport layer and an electrode layer arranged in sequence on the substrate side, the substrate can be a silicon battery, a conductive glass or other membrane, light passes through the electrode layer and the hole transport layer and is incident on the perovskite layer, photogenerated carriers occur on the perovskite layer, and then holes enter the hole transport layer, and electrons enter the electron transport layer, the hole transport layer is a self-assembled monolayer material (SAMs material), and the self-assembled monolayer material as a hole transport layer material (1) can provide excellent hole conductivity and improve the photoelectric conversion efficiency of the battery, (2) form a stable interface between the perovskite interfaces, reduce defects, reduce non-radiative recombination, and thus enhance the overall performance and stability of the battery. (3) It has strong adjustability, and its electronic properties can be optimized by changing the molecular structure, further improving the battery efficiency. (4) It has good film-forming properties and exhibits strong durability under harsh environmental conditions, ensuring long-term stable operation of the battery. (5) The preparation process of SAMs materials is environmentally friendly, simple in process, and has low cost in industrial applications.

[0006] The present invention further provides a connection layer between the hole transport layer and the perovskite layer, and an inorganic material is provided in the connection layer or the materials of the connection layer are all inorganic materials, and the light and heat stability is high. The inorganic material is selected from a combination of at least one or more of nitrides, sulfides, and oxides, that is, a compound containing -N, -O, and -S. On the one hand, such compounds have little effect on carriers and do not affect the tunneling effect of holes, and on the other hand, they can form a bond with the perovskite material.

[0007] As a preferred embodiment, the connecting layer is a sulfide or / and an oxide, and may contain only sulfide, only oxide, or both sulfide and oxide. The sulfide and oxide are mixed in a set ratio to form the connecting layer, and preferably the mixing ratio of sulfide to oxide is 1:5-5:1; more preferably, one of aluminum oxide, titanium oxide, zinc oxide, and silicon oxide is mixed with zinc sulfide. The thickness of the connecting layer is 1-5nm.

[0008] As a preferred solution, the connection layer includes at least two layers, one of which is a sulfide layer, preferably zinc sulfide, and the other is an oxide layer, preferably one of aluminum oxide, titanium oxide, zinc oxide, and silicon oxide. The sulfide layer is connected to the perovskite layer, and the -S bond has a very strong ability to coordinate with the perovskite, especially the lead element, so it can form a good passivation effect and promote the crystallization of the perovskite. The oxide layer is connected to the hole transport layer. The material layer has a low water vapor permeability and a dense structure. It serves as a barrier layer to protect the SAMs material and prevent water vapor from corroding the hole transport layer.

[0009] As a preferred embodiment, the connecting layer includes two layers, one of which is an oxide layer, and the other is a mixed layer of sulfide and nitride, the oxide is selected from one of aluminum oxide, titanium oxide, zinc oxide, and silicon oxide, the sulfide is zinc sulfide, and the nitride is selected from aluminum nitride and silicon nitride. The oxide layer has a low water vapor permeability and a dense structure. It serves as a barrier layer to protect the SAMs material and prevent water vapor from corroding the hole transport layer. On the one hand, the mixed layer of sulfide and nitride can form a specific passivation layer to guide the oriented crystallization of perovskite and enhance the stability of the perovskite layer. On the other hand, it forms a coordination bond with the perovskite to increase the connection strength between the connecting layer and the perovskite layer, thereby increasing the connection strength between the perovskite layer and the hole transport layer.

[0010] As a preferred embodiment, the thickness of the connecting layer is 1-5 nm, which can ensure the connection strength between the perovskite layer and the hole transport layer, prevent the hole transport layer and the perovskite layer from detaching, and ensure the tunneling efficiency of carriers in the film layer.

[0011] As a preferred method, the connecting layer is deposited on the hole transport layer in the form of atomic deposition. The atomic deposition structure is dense and can be like a dense "quilt" that can be tightly pressed on the SAMs layer so that it cannot be separated from the substrate. In addition, the film layer formed by atomic deposition has few defects, and the non-radiative recombination efficiency of carriers during transmission is low.

[0012] As a preferred embodiment, the hole transport layer material is [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), or / and (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid (Me-4PACz); poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), and the perovskite layer material is a lead-containing material, which can form strong interactions such as Pb-O / S / N with the connecting layer, further passivate the perovskite interface, and improve the interface performance.

[0013] As a preferred embodiment, the inorganic material is selected from one or more of aluminum oxide, titanium oxide, zinc oxide, silicon oxide, aluminum nitride, silicon nitride and zinc sulfide.

[0014] As a preferred embodiment, the perovskite layer material is capable of forming ABX 3 A is an organic or inorganic cation, B is a lead ion, X is a halogen, A is a methylamine ion, a formamidine ion, a Cs + The preparation method can be one or more of spin coating, blade coating, evaporation, etc., and the preferred perovskite material is MAI and PbI 2 MAPbI 3 ;FAI and PbI 2 Formed FAPbI 3 And the hybrid perovskite Cs0.05 FA 0.85 MA 0.10 Pb(I 0.95 Br 0.05 ) 3 .

[0015] The present invention also provides a method for preparing an inverted perovskite battery containing a self-assembled monolayer, the method comprising the following steps:

[0016] Obtaining a substrate;

[0017] Forming a hole transport layer on a substrate or forming a hole transport layer after forming a first spacer layer on a substrate;

[0018] forming a connection layer on the hole transport layer;

[0019] fabricating a perovskite layer on the connecting layer;

[0020] forming an electron transport layer on the perovskite layer or forming an electron transport layer after forming a second spacer layer on the perovskite layer;

[0021] An electrode layer is fabricated on the electron transport layer or an electrode layer is fabricated after a third spacer layer is fabricated on the electron transport layer; the connection layer contains an inorganic material, and the inorganic material is selected from one or more of nitrides, sulfides, and oxides;

[0022] The first spacer layer, the second spacer layer or the third spacer layer is one or more of a passivation layer, a modification layer, a transition layer, a light regulation layer and the like.

[0023] As a preferred embodiment, one method for preparing the connecting layer is: using atomic deposition to deposit sulfide, oxide or nitride on the hole transport layer, and after deposition to a certain thickness, stopping deposition to obtain the connecting layer. Preferably, an aluminum oxide film is deposited, and the deposition method is: using atomic deposition, trimethylaluminum as an aluminum source, water as an oxidant, and a deposition temperature of 80-300°C. First, a TMA (trimethylaluminum) pulse of 0.1-5 seconds is performed, followed by a 2-100 second inert gas purge, followed by a 0.1-5 second water pulse, and finally a 2-100 second purge again to remove by-products. The working pressure of the reaction chamber is maintained at 1-50 Torr, and the deposition is cyclic, and finally a 3nm thick aluminum oxide film is formed.

[0024] The second preparation method is: deposit an oxide layer on the hole transport layer by atomic deposition, adjust the deposition parameters after the deposition is completed, deposit a sulfide layer on the oxide layer, and stop the deposition after the deposition reaches a certain thickness to obtain a connecting layer. The specific preparation method is preferably: (1) A 3nm thick aluminum oxide film is prepared on the hole transport layer by ALD (atomic deposition), using trimethylaluminum as the aluminum source and water as the oxidant, and the deposition temperature is 150°C. First, a 0.3 second TMA pulse is performed, followed by a 15 second inert gas purge, followed by a 0.3 second water pulse, and finally a 15 second purge again to remove by-products. The working pressure of the reaction chamber is usually maintained at 5 Torr, and finally a thickness of 3nm is formed. (2) A 2nm thick sulfide layer is prepared by ALD, and the temperature of the reaction chamber is set between 150-250°C to optimize the adsorption and reaction of the precursor. When a lead source (such as dimethyl lead) is introduced, the gas flow rate is set to 20-50sccm and the duration is about 1-5 seconds, so that it forms a single atomic layer on the substrate. Next, an inert gas (such as nitrogen or argon) is used for purification, and the gas flow rate is usually 30-60sccm and the duration is 10-20 seconds. Then, when a sulfur source (such as hydrogen sulfide) is introduced, the flow rate can be set to 10-30sccm and the reaction time is 1-5 seconds. After that, an inert gas is used for cleaning again, and the flow rate and time are the same as the previous step, and then the cycle is repeated until the desired film thickness is reached. The general target thickness may be between 1-5 nanometers, and 20-40 cycles are usually required. Finally, after the deposition is completed, annealing can be performed at a temperature of 200-300°C to improve the crystallinity and electrical properties of the PbS film. These specific parameters help to achieve high uniformity and high-quality lead sulfide films.

[0025] As a preferred embodiment, a method for preparing a hole transport layer is as follows: (1) mixing MeO-2PACz with an ethanol solution to obtain a MeO-2PACz solution, filtering with a filter element to remove large particles, and reserving the filtered solution for later use; (2) spin coating the filtered solution on a substrate; and (3) annealing to obtain a hole transport layer.

[0026] The second preparation method is as follows: (1) Me-4PACz is mixed with an isopropanol solution to obtain a Me-4PACz solution, and the solution is filtered using a filter element to remove large particles, and the filtered solution is used for later use; (2) the filtered solution is slit coated on a substrate;

[0027] The third preparation method is as follows: (1) mixing PTAA with chlorobenzene solution to obtain a PTAA solution, filtering with a filter element to remove large particles, and reserving the filtered solution for later use; (2) spraying the filtered solution on a substrate; and (3) annealing to obtain a hole transport layer.

[0028] As a preferred solution, one method for preparing the perovskite layer is: (1) preparing MAI+PbI 2 Solution: PbI 2 MAI and PbI were dissolved in a mixed solvent of DMF (NN dimethylformamide) and DMSO (dimethyl sulfoxide), heated until completely dissolved, and filtered with a filter element to remove larger particles in the solution to obtain MAI+PbI 2 (2) Prepare MAI+PbI 2 The solution is spin-coated on the inorganic modification layer, and anti-solvent toluene is evenly dropped on the film layer during the spin-coating process. The film is then annealed in a nitrogen atmosphere and cooled for later use to form a thick perovskite film layer.

[0029] The second preparation method is: (1) Preparation of FAI+PbI 2 Solution: PbI 2 Dissolve FAI and PbI in a mixed solvent of DMF (NN dimethylformamide) and DMSO (dimethyl sulfoxide), heat until completely dissolved, and use a filter to remove larger particles in the solution to obtain FAI+PbI 2 (2) Prepare FAI+PbI 2 The solution is spin-coated on the inorganic modification layer, and anti-solvent toluene is evenly dropped on the film layer during the spin-coating process. The film is then annealed in a nitrogen atmosphere and cooled for later use to form a thick perovskite film layer.

[0030] The third preparation method is: (1) preparing Cs 0.05 FA 0.85 MA 0.10 Pb(I 0.95 Br 0.05 ) 3 Solution: PbI 2 、FAI、CsI、CsBr、PbBr 2 Dissolve in a mixed solvent of DMF (NN dimethylformamide) and DMSO (dimethyl sulfoxide), heat until completely dissolved, and use a filter element to filter and remove larger particles in the solution to obtain a solution. (2) Spin-coat the prepared solution on the inorganic modification layer, and evenly drop the anti-solvent chlorobenzene on the film layer during the spin coating process, then anneal in a nitrogen atmosphere, cool and set aside to form a thick perovskite film layer.

[0031] As a preferred solution, the preparation method of the electron transport layer is as follows: (1) using a vacuum evaporation device to evaporate C by thermal evaporation 60 Materials are used to form an electron transport layer on the perovskite film layer, and the evaporation vacuum degree is below 7*10-4Pa.

[0032] As a preferred solution, after preparing the electron transport layer, a hole blocking layer is prepared on the electron transport layer. The preparation method is: using vacuum evaporation equipment, evaporating BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or bathocuproin) material by thermal evaporation to form a hole blocking layer on the electron transport layer, and the evaporation vacuum is below 7*10-4Pa.

[0033] The beneficial effects of the present invention include: the present invention uses a self-assembled monolayer as a hole transport layer material of the inverse perovskite, which is beneficial to improving the hole transport efficiency and the photoelectric conversion efficiency of the battery;

[0034] The self-assembled monolayer itself will degrade under the condition of light and heating; and the connection between the self-assembled monolayer and the upper and lower interfaces will desorb and detach under the environment of light, humidity, etc., which seriously affects the performance of the device. In the present invention, a connecting layer is deposited on the self-assembled monolayer, and the connecting layer is an inorganic material or contains an inorganic material, and has a stable structure and components. It tightly covers and protects the self-assembled monolayer like a quilt, so that it can run stably in the device and will not fall off;

[0035] The inorganic material in the present invention is selected from nitrides, sulfides or oxides, which form strong interactions such as Pb-O / S / N with the perovskite components, thereby passivating the perovskite interface;

[0036] The connection layer in the present invention interacts with the perovskite to guide the perovskite to crystallize in a directional manner and improve the crystallization performance of the perovskite.

[0037] The present invention uses a single passivation molecule and multiple defects to generate binding energy between each defect and the molecule, thereby enhancing the binding energy between the defect and the passivation molecule, thereby ensuring that the molecule does not fall off under the action of an external field and ensuring that the connection layer has a continuous passivation effect.

[0038] Unless otherwise specified, any range described in the present invention includes any end value and any value between the end values ​​and any sub-range formed by the end value or any value between the end values. All raw materials of the present invention are not particularly limited in purity, and the present invention preferably adopts analytically pure. All raw materials of the present invention, their sources and abbreviations belong to conventional sources and abbreviations in this field, and are clear and definite in the field of their related uses. Those skilled in the art can purchase them from the market or prepare them by conventional methods according to the abbreviations and corresponding uses. All percentages of the present invention are mass percentages unless otherwise specified.

[0039] "At least one" means one or more, and "more" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the previous and next associated objects are in an "or" relationship. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, at least one of a, b or c can mean: a, b, c, the combination of a and b, the combination of a and c, the combination of b and c, or the combination of a, b and c, where a, b, c can be single or plural. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Perovskite photovoltaic device structure diagram;

[0041] FIG. 2 is the efficiency attenuation curves of Comparative Example 1 and Example 1 under 85°C + 85% humidity aging conditions;

[0042] Figure 3 Efficiency attenuation curves of Comparative Example 2 and Example 2 under a sunlight irradiation aging condition;

[0043] In the figure, 1 is substrate, 2 is hole transport layer, 3 is inorganic protective layer, 4 is perovskite layer, 5 is electron transport layer, 6 is hole blocking layer, and 7 is electrode. DETAILED DESCRIPTION

[0044] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0045] Unless otherwise specified, any range described in the present invention includes any end value and any value between the end values ​​and any sub-range formed by the end value or any value between the end values. All raw materials of the present invention are not particularly limited in purity, and the present invention preferably adopts analytically pure materials. All raw materials of the present invention, their sources and abbreviations are conventional sources and abbreviations in the art, and are clear and definite in the field of their related uses. Those skilled in the art can purchase them from the market or prepare them by conventional methods according to the abbreviations and corresponding uses.

[0046] "At least one" means one or more, and "plurality" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the objects associated before and after are in an "or" relationship. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, at least one of a, b or c can mean: a, b, c, the combination of a and b, the combination of a and c, the combination of b and c, or the combination of a, b and c, where a, b, c can be single or multiple. The inorganic protective layers involved below all refer to the connecting layers mentioned above.

[0047] Example 1

[0048] This embodiment is an inverted (pin) conventional bandgap perovskite solar cell, and the preparation method includes the following steps:

[0049] S01 Get Base 1

[0050] ITO glass was used as the substrate. The ITO glass substrate was first ultrasonically cleaned in a detergent and deionized water for 20 minutes each, then ultrasonically cleaned in acetone for 20 minutes, and finally ultrasonically cleaned in isopropyl alcohol (IPA) for 20 minutes. It was then blown dry with a nitrogen gun and placed in a UV ozone processor for 15 minutes for use.

[0051] S02 Preparation of hole transport layer 2

[0052] (1) 1 mg of MeO-PACz was mixed with 2 mL of ethanol solution to obtain a 0.5 mg / mL MeO-2PACz solution, which was filtered through a 0.45 μm filter element to remove large particles, and the filtered solution was set aside;

[0053] (2) Spin-coat the filtered solution on ITO glass at a spin-coating rate of 3500 rpm for 40 s;

[0054] (3) Annealing at 125°C for 10 min to obtain a MeO-2PACz hole transport layer with a thickness of about 2 nm.

[0055] Preparation of S03 Inorganic Protective Layer 3

[0056] A 3nm thick aluminum oxide film was prepared by ALD (atomic deposition), using trimethylaluminum as the aluminum source and water as the oxidant, at a deposition temperature of 150°C. First, a 0.3 second TMA pulse was performed, followed by a 15 second inert gas purge, followed by a 0.3 second water pulse, and finally a 15 second purge to remove byproducts. The working pressure of the reaction chamber was usually maintained at 5 Torr, and finally a thickness of 3nm was formed.

[0057] Preparation of S04 perovskite film layer 4

[0058] (1) Preparation of MAI+PbI 2 Solution: 461 mg of PbI 2 159 mg of MAI was dissolved in 0.85 mL of DMF (NN dimethylformamide) and 0.15 mL of DMSO (dimethyl sulfoxide), heated at 70 °C and stirred for 1 hour until completely dissolved, and a 0.45 μm filter was used to filter out larger particles in the solution to obtain MAI+PbI 2 Solution.

[0059] (2) Prepare MAI+PbI 2 The solution was spin-coated on the inorganic modification layer at a spin-coating rate of 4000 rpm for 30 seconds. At the 10th second of spin-coating, 160 μL of anti-solvent toluene was evenly added to the film layer, followed by annealing at 100°C for 30 minutes in a nitrogen atmosphere, and then cooled for use to form a perovskite film layer with a thickness of 450 nm.

[0060] Preparation of S05 electron transport layer 5

[0061] Using vacuum evaporation equipment, C is evaporated by thermal evaporation. 60 Materials, forming a 20nm electron transport layer on the perovskite film layer, the evaporation vacuum degree is 7*10 -4 Below Pa.

[0062] Preparation of S06 hole blocking layer 6:

[0063] Vacuum evaporation equipment was used to evaporate BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or bathocuproin) material by thermal evaporation to form an 8nm hole blocking layer on the electron transport layer. The evaporation vacuum was 7*10 -4 Below Pa.

[0064] Preparation of S07 electrode 7

[0065] A 100 nm copper (Cu) layer is deposited on the surface of the hole blocking layer by thermal evaporation as an electrode.

[0066] Embodiment 2:

[0067] This embodiment is an inverted (pin) conventional bandgap perovskite solar cell, and the preparation method includes the following steps:

[0068] S01 Get the base

[0069] ITO glass was used as the substrate. The ITO glass substrate was first ultrasonically cleaned in a detergent and deionized water for 20 minutes each, then ultrasonically cleaned in acetone for 20 minutes, and finally ultrasonically cleaned in isopropyl alcohol (IPA) for 20 minutes. It was then blown dry with a nitrogen gun and placed in a UV ozone processor for 15 minutes for use.

[0070] S02 Preparation of hole transport layer

[0071] (1) 1 mg of MeO-2PACz was mixed with 2 mL of ethanol solution to obtain a 0.5 mg / mL MeO-2PACz solution, and the solution was filtered through a 0.45 μm filter element to remove large particles. The filtered solution was set aside for later use;

[0072] (2) Spin-coat the filtered solution on ITO glass at a spin-coating rate of 3500 rpm for 40 s;

[0073] (3) Annealing at 125°C for 10 min to obtain a MeO-2PACz hole transport layer with a thickness of about 2 nm.

[0074] Preparation of S03 Inorganic Protective Layer

[0075] (1) A 3 nm thick aluminum oxide film is deposited by ALD, using trimethylaluminum as the aluminum source and water as the oxidant at a deposition temperature of 150°C. First, a 0.3 second TMA pulse is performed, followed by a 15 second inert gas purge, followed by a 0.3 second water pulse, and finally a 15 second purge to remove byproducts. The operating pressure of the reaction chamber is usually maintained at 5 Torr, and finally a 3 nm thick aluminum oxide film is formed.

[0076] (2) A 2 nm thick sulfide layer was prepared on the aluminum oxide film layer using ALD (atomic deposition). The temperature of the ALD reaction chamber was set at 250°C to optimize the adsorption and reaction of the precursor. The deposition steps of the sulfide were:

[0077] a. A lead source, dimethyl lead, is introduced into the reaction chamber with a gas flow rate of 50 sccm for a duration of about 4 seconds to form a single atomic layer on the substrate.

[0078] b Use inert gas to purify the reaction chamber with a flow rate of 60 sccm and a duration of 15 seconds.

[0079] c. Introduce hydrogen sulfide into the reaction chamber with a flow rate of 20 sccm and a reaction time of 3 seconds.

[0080] d. Use inert gas to clean the reaction chamber again. The flow rate and introduction time of the inert gas are the same as those in step b.

[0081] e. Repeat steps a to d until the film thickness is 2 nm.

[0082] After deposition, annealing treatment is performed at 200 °C to improve the crystallinity and electrical properties of the PbS film and obtain a high-uniformity and high-quality lead sulfide film.

[0083] Preparation of S04 perovskite film

[0084] (1) Preparation of MAI+PbI 2 Solution: 461 mg of PbI 2 159 mg of MAI was dissolved in 0.85 mL of DMF (NN dimethylformamide) and 0.15 mL of DMSO (dimethyl sulfoxide), heated at 70 °C and stirred for 1 hour until completely dissolved, and a 0.45 μm filter was used to filter out larger particles in the solution to obtain MAI+PbI 2 Solution.

[0085] (2) Prepare MAI+PbI 2 The solution was spin-coated on the inorganic protective layer at a spin-coating rate of 4000 rpm for 30 seconds. At the 10th second of spin-coating, 160 μL of anti-solvent toluene was evenly added to the film layer, followed by annealing at 100° C. for 30 minutes in a nitrogen atmosphere, and then cooled for use to form a perovskite film layer with a thickness of 450 nm.

[0086] Preparation of S05 electron transport layer

[0087] (1) Using vacuum evaporation equipment, evaporate C by thermal evaporation 60 Materials, forming a 20nm electron transport layer on the perovskite film layer, the evaporation vacuum degree is 7*10 -4 Below Pa.

[0088] Preparation of S06 hole blocking layer:

[0089] Vacuum evaporation equipment was used to evaporate BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or bathocuproin) material by thermal evaporation to form an 8nm hole blocking layer on the electron transport layer. The evaporation vacuum was 7*10 -4 Below Pa.

[0090] Preparation of S07 electrode

[0091] A 100 nm copper (Cu) layer is deposited on the surface of the hole blocking layer by thermal evaporation as an electrode.

[0092] Example 3

[0093] This embodiment is an inverted (pin) conventional bandgap perovskite solar cell, and the preparation method includes the following steps:

[0094] S01 Get the base

[0095] ITO glass was used as the substrate. The ITO glass substrate was first ultrasonically cleaned in a detergent and deionized water for 20 minutes each, then ultrasonically cleaned in acetone for 20 minutes, and finally ultrasonically cleaned in isopropyl alcohol (IPA) for 20 minutes. It was then blown dry with a nitrogen gun and placed in a UV ozone processor for 15 minutes for use.

[0096] S02 Preparation of hole transport layer

[0097] (1) 1 mg of MeO-2PACz was mixed with 2 mL of ethanol solution to obtain a 0.5 mg / mL MeO-2PACz solution, and the solution was filtered through a 0.45 μm filter element to remove large particles. The filtered solution was set aside for later use;

[0098] (2) Spin-coat the filtered solution on ITO glass at a spin-coating rate of 3500 rpm for 40 s;

[0099] (3) Annealing at 125°C for 10 min to obtain a MeO-2PACz hole transport layer with a thickness of about 2 nm.

[0100] Preparation of S03 Inorganic Protective Layer

[0101] A 3nm thick aluminum oxide film was prepared by ALD (atomic deposition), using trimethylaluminum as the aluminum source and water as the oxidant, at a deposition temperature of 150°C. First, a 0.3 second TMA pulse was performed, followed by a 15 second inert gas purge, followed by a 0.3 second water pulse, and finally a 15 second purge to remove byproducts. The working pressure of the reaction chamber was usually maintained at 5 Torr, and finally a thickness of 3nm was formed.

[0102] Preparation of S04 perovskite film

[0103] (1) Preparation of FAI+PbI 2 Solution: 461 mg of PbI 2172 mg of FAI was dissolved in 0.90 mL of DMF (NN dimethylformamide) and 0.10 mL of DMSO (dimethyl sulfoxide), heated at 70 °C and stirred for 1 hour until completely dissolved, and a 0.45 μm filter was used to filter out larger particles in the solution to obtain FAI+PbI 2 Solution.

[0104] (2) Spin-coat the prepared solution on the inorganic modification layer at a spin-coating rate of 4000 rpm for 30 seconds. At the 15th second of spin-coating, evenly add 200 μL of anti-solvent chlorobenzene on the film layer, then anneal at 150°C for 10 minutes in a nitrogen atmosphere, anneal at 150°C for 10 minutes in air, cool and set aside to form a perovskite film layer with a thickness of 500 nm.

[0105] Preparation of S05 electron transport layer

[0106] Using vacuum evaporation equipment, C is evaporated by thermal evaporation. 60 Materials, forming a 20nm electron transport layer on the perovskite film layer, the evaporation vacuum degree is 7*10 -4 Below Pa.

[0107] Preparation of S06 hole blocking layer:

[0108] Vacuum evaporation equipment was used to evaporate BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or bathocuproin) material by thermal evaporation to form an 8nm hole blocking layer on the electron transport layer. The evaporation vacuum was 7*10 -4 Below Pa.

[0109] Preparation of S07 electrode

[0110] A 120 nm silver (Ag) layer is deposited on the surface of the hole blocking layer by thermal evaporation as an electrode.

[0111] Example 4

[0112] This embodiment is an inverted (pin) conventional bandgap perovskite solar cell, and the preparation method includes the following steps:

[0113] S01 Get the base

[0114] Using FTO glass as the substrate, the ITO glass substrate was first ultrasonically cleaned in a detergent and deionized water for 20 minutes each, then ultrasonically cleaned in acetone for 20 minutes, and finally ultrasonically cleaned in isopropyl alcohol (IPA) for 20 minutes, then blown dry with a nitrogen gun, and placed in a UV ozone processor for 15 minutes for use.

[0115] S02 Preparation of hole transport layer

[0116] (1) 0.75 mg of Me-4PACz was mixed with 1 mL of isopropanol solution to obtain a 0.75 mg / mL Me-4PACz solution, and the solution was filtered through a 0.45 μm filter element to remove large particles. The filtered solution was used for later use;

[0117] (2) Spin-coat the filtered solution on FTO glass at a rate of 3500 rpm for 40 s;

[0118] (3) Annealing at 125°C for 10 min to obtain a Me-4PACz hole transport layer with a thickness of about 2 nm.

[0119] Preparation of S03 Inorganic Protective Layer

[0120] A 3nm thick aluminum oxide film layer was prepared by ALD (atomic deposition), using trimethylaluminum as the aluminum source and water as the oxidant, at a deposition temperature of 150°C. First, a 0.3 second TMA pulse was performed, followed by a 15 second inert gas purge, followed by a 0.3 second water pulse, and finally a 15 second purge to remove by-products. The working pressure of the reaction chamber is usually maintained at 5 Torr, and finally a 3nm thick aluminum oxide film layer is formed.

[0121] Preparation of S04 perovskite film

[0122] (1) Preparation of FAI+PbI 2 Solution: 461 mg of PbI 2 172 mg of FAI was dissolved in 0.90 mL of DMF (NN dimethylformamide) and 0.10 mL of DMSO (dimethyl sulfoxide), heated at 70 °C and stirred for 1 hour until completely dissolved, and a 0.45 μm filter was used to filter out larger particles in the solution to obtain FAI+PbI 2 Solution.

[0123] (2) Spin-coat the prepared solution on the inorganic modification layer at a spin-coating rate of 4000 rpm for 30 seconds. At the 15th second of spin-coating, evenly add 200 μL of anti-solvent chlorobenzene on the film layer, then anneal at 150°C for 10 minutes in a nitrogen atmosphere, anneal at 150°C for 10 minutes in air, cool and set aside to form a perovskite film layer with a thickness of 500 nm.

[0124] Preparation of S05 electron transport layer

[0125] Using vacuum evaporation equipment, C is evaporated by thermal evaporation. 60 Materials, forming a 20nm electron transport layer on the perovskite film layer, the evaporation vacuum degree is 7*10 -4 Below Pa.

[0126] Preparation of S06 hole blocking layer

[0127] Vacuum evaporation equipment was used to evaporate BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline or bathocuproin) material by thermal evaporation to form an 8nm hole blocking layer on the electron transport layer. The evaporation vacuum was 7*10 -4 Below Pa.

[0128] Preparation of S07 electrode

[0129] A 120 nm silver (Ag) layer is deposited on the surface of the hole blocking layer by thermal evaporation as an electrode.

[0130] Comparative Example 1

[0131] The difference from Example 1 is that no inorganic protective layer is provided.

[0132] Comparative Example 2

[0133] The difference from Example 2 is that no inorganic protective layer is provided.

[0134] The efficiency changes of Example 1 and Comparative Example 1 were tested under 85°C and 85% humidity aging conditions. The results are as follows: Figure 2 It can be seen that the efficiency decayed to 86.1% at 568h, and the control ratio decayed to 76.7%. The inorganic protective layer is beneficial to enhance the stability of perovskite efficiency.

[0135] The efficiency changes of Example 2 and Comparative Example 2 were tested under one sunlight and room temperature. The results are as follows Figure 3 It can be seen that the efficiency decays to 84.3% after 800 hours, and the control ratio decays to 75.7%, indicating that the inorganic protective layer is beneficial to enhancing the stability of perovskite efficiency.

[0136] The efficiency changes of Examples 1 to 4 were tested under aging conditions of 85°C and 85% humidity. After 568 hours, the efficiency decayed to 86.1%, 88.2%, 86.3%, and 87.6%, respectively. It can be seen that the batteries with the addition of the inorganic protective layer showed good thermal stability under high temperature conditions.

[0137] The efficiency of Examples 1 to 4 was aged under one sunlight and room temperature conditions. After 800 hours, the efficiency decayed to 84.1%, 84.3%, 83.9%, and 83.8%, respectively. It can be seen that the batteries with the addition of the inorganic protective layer showed good light stability under strong light conditions.

[0138] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. An inverse perovskite cell containing a self-assembled monolayer, comprising a hole transport layer, a perovskite layer, an electron transport layer and an electrode layer arranged in sequence from the substrate side, characterized in that: The hole transport layer is a self-assembled monolayer material. A connecting layer is provided between the hole transport layer and the perovskite layer. Inorganic material is provided in the connecting layer. The inorganic material is a combination of one or more of nitride, sulfide and oxide.

2. The perovskite cell containing a self-assembled monolayer according to claim 1, characterized in that: The connection layer includes sulfide and oxide, and the sulfide and oxide are mixed in a set ratio to form the connection layer.

3. The inverse perovskite cell containing a self-assembled monolayer according to claim 1, characterized in that: The connecting layer includes at least two layers, one of which is a sulfide layer and the other is an oxide layer. The sulfide layer is close to the perovskite layer, and the oxide layer is close to the hole transport layer.

4. The inverse perovskite cell containing a self-assembled monolayer according to claim 2 or 3, characterized in that: The thickness of the connecting layer is 1-5 nm, and the connecting layer is deposited on the hole transport layer in the form of atomic deposition.

5. The inverse perovskite cell containing a self-assembled monolayer according to claim 1, characterized in that: The hole transport layer material is [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid or / and (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid; The perovskite layer material is a lead-containing material.

6. The inverse perovskite cell containing a self-assembled monolayer according to claim 1, characterized in that: The inorganic material is selected from one or more of aluminum oxide, titanium oxide, zinc oxide, silicon oxide, aluminum nitride, silicon nitride, zinc sulfide, and lead sulfide.

7. The inverse perovskite cell containing a self-assembled monolayer according to claim 1, characterized in that: The connection layer includes a lead sulfide layer connected to the perovskite layer and an aluminum oxide layer connected to the hole transport layer.

8. The inverse perovskite cell containing a self-assembled monolayer according to claim 1, characterized in that: The perovskite layer material at least includes MAPbI3, FAPbI3, Cs 0.05 FA 0.85 MA 0.10 Pb(I 0.95 Br 0.05 )One of 3.

9. A method for preparing an inverse perovskite cell containing a self-assembled monolayer, characterized in that: The method comprises the following steps: obtaining a substrate; preparing a hole transport layer; Make a connection layer; Making a perovskite layer; fabricating an electron transport layer; manufacturing an electrode layer; The connection layer contains an inorganic material, and the inorganic material is selected from one or more of nitrides, sulfides, and oxides.

10. The preparation method according to claim 9, characterized in that: The connecting layer includes a lead sulfide layer and an aluminum oxide layer, and both the lead sulfide layer and the aluminum oxide layer are formed by atomic deposition. The preparation method of the lead sulfide layer is: (1) introducing a lead source into the atomic deposition reaction chamber to obtain a single atomic layer, with the gas flow rate set to 20-50 sccm and the time being 1-5 s; (2) introducing an inert gas to purify the reaction chamber; (3) introducing a sulfur source into the reaction chamber at a gas flow rate of 10-30 sccm for a time of 1-5 s; (4) repeating steps (1) to (3) until a lead sulfide layer of a desired thickness is formed; The preparation method of the aluminum oxide layer is: An aluminum oxide layer is prepared using trimethylaluminum as an aluminum source and water as an oxidant at a deposition temperature of 150 to 250°C. (1) trimethylaluminum is introduced, (2) an inert gas is introduced for purging, and (3) a water pulse is introduced. Steps (1) to (3) are repeated to obtain an aluminum oxide layer of a desired thickness.

Citation Information

Patent Citations

  • Perovskite solar cell, preparation method thereof and electronic product

    CN117641946A

  • Composite hole transport layer and preparation method thereof, and inverted perovskite solar cell

    CN118139431A

  • Solar cell and preparation method thereof

    CN119173053A

  • Conductive substrate, perovskite substrate using the conductive substrate and solar cell using the perovskite substrate

    US20240188428A1

Cited By

  • Photovoltaic device, preparation method and photovoltaic equipment

    CN121194615A